2017
DOI: 10.25077/adj.v5i2.74
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengetahuan Dan Sikap Dengan Tindakan Mahasiswa Program Profesi Dokter Gigi RSGMP Universitas Andalas Terhadap Pengendalian Infeksi

Abstract: Background : In dentistry, level of risk on cross infection can be said very high. This is due to the teeth treatment, the operator may have direct contact with saliva and patient’s blood. The implementation of standard precautions is very important in clinical practice because in addition to it must be obeyed, it can avoid the operator and the patient to the cross infection. The purpose : To determine the relationship between knowledge and attitudes with the practices toward infection control of clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The type of research used in this study is observational analytic with a crosssectional study approach. Each research subject is only carried out once and all research subjects are observed at the same time (Utami and Putri, 2013). To answer the problem through careful measurement techniques on certain variables, so as to produce conclusions that can be generalized, regardless of the context of time and situation as well as the type of data collected.…”
Section: Metodsmentioning
confidence: 99%
“…The type of research used in this study is observational analytic with a crosssectional study approach. Each research subject is only carried out once and all research subjects are observed at the same time (Utami and Putri, 2013). To answer the problem through careful measurement techniques on certain variables, so as to produce conclusions that can be generalized, regardless of the context of time and situation as well as the type of data collected.…”
Section: Metodsmentioning
confidence: 99%
“…In Yogyakarta, throughout 2014, there were 2,933 cases of HIV/AIDS with the highest cases being in the city of Yogyakarta as much as 27.3%. The number of infected health workers was as many as 300 officers with the number of injuries to dentists was 36% and 4% were dental students [4].…”
Section: Introductionmentioning
confidence: 99%
“…Dentists are always in direct or indirect contact with the patient's blood and saliva. The spread of infection can occur by inhalation through the respiratory process, so dentists have a high risk for dangerous infectious diseases caused by viruses and bacteria [3]. Patients who cough, sneeze, or receive dental treatment using a high-speed handpiece produce aerosolized secretions, saliva, or blood in the vicinity.…”
Section: Introductionmentioning
confidence: 99%